2021
DOI: 10.2147/opth.s205147
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Visual Acuity After Treatment of Neovascular Age-Related Macular Degeneration – Current Perspectives

Abstract: Visual acuity is a key outcome measure in the treatment of neovascular age-related macular degeneration (nAMD) using anti-vascular endothelial growth factor agents. Large variations in visual responses between individuals within clinical trials and real-world studies may relate to underlying differences in patient and treatment factors. Most notably, a better baseline visual acuity, younger age and smaller choroidal neovascularization lesion size have been strongly associated with achieving better visual outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 127 publications
(198 reference statements)
1
12
0
Order By: Relevance
“…Further, anatomical outcomes assessed by OCT, such as CMT changes and the presence of retinal fluid (IRF, SRF, and SHRM), are important indicators of disease activity in nAMD patients [ 14 , 23 ]. In our study, significant improvement was observed in CMT from baseline to week 48 in eyes treated with both the drugs.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Further, anatomical outcomes assessed by OCT, such as CMT changes and the presence of retinal fluid (IRF, SRF, and SHRM), are important indicators of disease activity in nAMD patients [ 14 , 23 ]. In our study, significant improvement was observed in CMT from baseline to week 48 in eyes treated with both the drugs.…”
Section: Discussionmentioning
confidence: 99%
“…At both time points, the majority of the brolucizumab patients were on a 12-week dosing interval compared to an 8-week dosing interval for aflibercept treated patients. Additionally, it has been shown that individuals with residual SRF at the end of the loading doses may have a negative impact on BCVA gains [ 15 , 23 ]. Our results indicate fewer eyes treated with brolucizumab with SRF presence than aflibercept after the loading doses, i.e., at weeks 8, 12 and 16.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations